2000
DOI: 10.1016/s0304-3878(00)00082-1
|View full text |Cite
|
Sign up to set email alerts
|

Supervision and performance: the case of World Bank projects

Abstract: and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercial gain-You may freely distribute the URL identifying the publication in the public portal Take down policy If you believe that this document breaches copyrigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 10 publications
(2 reference statements)
1
70
1
Order By: Relevance
“…To the extent that there are measurement errors, the mistakes should be unbiased, evenly distributed, and thus not effect final results (i.e., noise). This database is widely used in economic research [52]. Table 1 lists all the independent variables along with the corresponding year.…”
Section: Independent Variablesmentioning
confidence: 99%
“…To the extent that there are measurement errors, the mistakes should be unbiased, evenly distributed, and thus not effect final results (i.e., noise). This database is widely used in economic research [52]. Table 1 lists all the independent variables along with the corresponding year.…”
Section: Independent Variablesmentioning
confidence: 99%
“…However, higher levels of resources spent on supervision and preparation were negatively, rather than positively, related to project success. In contrast, Kilby (2000) and Dollar and Levin (2005), using data from World Bankfunded projects, found that early supervision does have a positive impact on the performance of projects.…”
Section: Development Effectiveness Reviewsmentioning
confidence: 99%
“…However, several of these studies also demonstrated difficulty in reaching consensus on the meaning and measure of project success. Kilby (2000) argues that project performance or success, which is a measure of the project's net contribution to the economy, cannot be fully assessed until all project costs and benefits are fully realised. That requires systematic collection of data after a project is completed.…”
Section: Development Effectiveness Reviewsmentioning
confidence: 99%
“…World Bank projects all too frequently fail to achieve their goals due to a number of problems that could be termed "managerial" and "organizational" (Kwak, 2002): imperfect project design, poor stakeholder management, delays between project identification and start-up, delays during project implementation, cost overruns, coordination failure, etc. (Youker, 1999;Kilby, 2000;Ahsan & Gunawan, 2010). This study investigated the effect of project training on project performance.…”
Section: Introductionmentioning
confidence: 99%